Recent and current advances in PET/CT imaging in the field of predicting epidermal growth factor receptor mutations in non-small cell lung cancer - Hu, Na; Yan, Gang; Wu, Yuhui; Wang, Li; Wang, Yang; Xiang, Yining; Lei, Pinggui; Luo, Peng (Frontiers in Oncology, 2022)
As tyrosine kinase inhibitor (TKI) is a significant treatment strategy applied to non-small cell lung cancer (NSLCC), it has been critically essential to identify epidermal growth factor receptor (EGFR) mutation status in management stratification. At present, detection of EGFR mutation status is established on the basis of tumor tissue acquired by biopsy or resection, which has many limitations. Therefore, there is a compelling need to develop noninvasive, rapid, and accurate methods for gene mutation detection. A growing number of researchers are trying to address these problems using approaches based on non-invasive molecular imaging. Positron emission tomography/computed tomography(PET/CT) has been widely applied in estimating patients with NSCLC accepting targeted treatment because its undoubted ability to obtain the molecular and genomic features of the tumor noninvasively. Recent studies have shown PET/CT serves as a method for precise quantification of EGFR mutation status in NSCLC patients, so as to achieve precision therapy. In this paper, we review the recent and current advances in PET/CT imaging within the field of predicting EGFR mutations in NSCLC.